Estudo dos constituintes químicos de duas amostras de própolis: Alto Santo - Ceará e Passa Quatro - Minas Gerais - Albuquerque, Irineu Lima de (2007)
Propolis, word has the Greek origin, and means city defense. Used in the beehive to forbid openings, guaranteeing protection against microorganisms. Several therapeutically properties were reported such as: bactericidal, fungicidal, antivirus, anti-inflammatory. Brazilian propolis can be classified in 13 groups, based on the physical-chemistry characteristics classified as: five in the South of Brazil (group 3), one in Southeast (group 12) and six in the Northeast (group 7). The present work has a goal the phytochemical investigation of two samples of propolis: one from Alto Santo - Ceará and other from Minas Gerais - Brasil and determination of biological activity. From a sample of propolis of Ceará, were identified: triterpenes (lupeol, acid canaric, lupenone and germanicone); flavonoids (kercetin, kanferol, acacetine, 3-(4-methoxyphenyl) acrilate of 2-(E)-2-methoxyphenil-5-(5-hydroxy-3,7-dimethoxy-4-oxo-4H-cromene-2-il). For the sample propolis of Minas Gerais popularly called “green propolis” were identified p-cumaric acid, (E)-3-(3,4-dihidroxyphenyl) propenoic acid and a mixture of acid ones: (E)-3-(4-hydroxyphenyl) propenoic acid, 3-phenylpropanoic acid and 3-(4-hydroxiphenil) propanoic acid. From lupeol a serie of derivative were obtained including oxidation and esters at carbon-3. Pure compounds and lupeol derivatives were identified by spectroscopic methods such as IR, 1H and 13C NMR and MS. Propolis extracts and pure compounds were evaluated for scavenger activity using DPPH (2,2-diphenyl,1-picril-hidrazil) bioassay and results showed very good activity for extracts and for flavonoids where as triterpens showed a week activity. The essential oil of the propolis from Minas Gerais obtained by hydrodestillation process was analyzed by CG-MS techniques and composition was defined as: oxygenated monoterpenes (0,30%), hydrocarbons sesquiterpenes (65,18%), sesquiterpenes oxigenated (23,64%), and derivatives of the cinamic acid (6,17%). Twenty constituent were identified representing 97.7% and major compound defined as: E-nelolidol (17,14%), E-cariofilene (13,38%) and selin-3,7(11)-dien (10,35%). The oil was characterized with high percentage of hydrocarbons sesquiterpenes and oxygenated sesquiterpenes. The green propolis of Minas Gerais was used as material for the lyophilized drug production. From the propolis water soluble together with L-lysine and a polymer PVP was obtained a power and it is using for biological tests as anticancer agent.